THE APPLICATION OF THE VALUES OF THE PROFIL PELAJAR PANCASILA IS CONCEPT OF KURIKULUM MERDEKA IN THE SUBJECT OF IPAS - Syarifuddin, Syarifuddin; Isya, De; Abdussahid, Abdussahid; Kusumawati, Yayuk (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI), 2024)
This study aims to determine the application of the profil pelajar Pancasila is concept kurikulum merdeka in IPAS subjects at SDN 55 Bima City. This research uses a qualitative descriptive method with the subject of the principal, IPAS subject teacher and grade IV students. The data collection techniques used by researchers to obtain the necessary data are; interviews, observation and documentation. The results of this study indicate that SDN 55 Kota Bima has implemented the values of the Pancasila learner profile at school well, both in the IPAS subject in grade IV and applied to habituation and school culture. The values of the Pancasila learner profile in question are faith, devotion to God Almighty and noble character, global diversity, cooperation, independence, creativity, and critical reasoning.